Effect of oral nutritional supplementation combined with impedance vectors for dry weight adjustment on the nutritional status, hydration status and quality of life in patients on chronic hemodialysis: A pilot study. (April 2023) - Nieves-Anaya, Iris; Várgas, Mónica B.; García, Olga P.; Biruete, Annabel; Kistler, Brandon; Atilano-Carsi, Ximena
Summary: Background & aims: Protein energy wasting frequently affect hemodialysis patients and contribute to the development of overhydration. The objective of this study was to assess the effect of oral nutritional supplementation (ONS) combined with bioelectrical vector analysis (BIVA) on the nutritional and hydration status and the quality of life (QoL) in hemodialysis (HD) patients. Methods: Thirty-two chronic HD patients were included in a 6-month randomized pilot study. Patients in SUPL group received a simultaneous intervention consisting of a personalized diet, 245 mL/d ONS and dry weight adjustment through BIVA. Patients in CON group received a personalized diet and dry weight adjustment by BIVA. Anthropometrical, biochemical, dietary, QoL, handgrip strength (HGS) and bioimpedance measurements were performed. Malnutrition Inflammation Score (MIS) was applied. Results: At the end of the intervention, moderate undernutrition decreased by 43.8% in SUPL group while in CON group, severe undernutrition increased by 13% (p < 0.04 between groups). In the adjusted covariance analysis, SUPL compared to CON group, increased HGS ( Δ 2.8 Kg vs Δ  −1.8 Kg, p = 0.003), serum albumin (Δ 0.29 g/dL vs Δ −0.03 g/dL, p = 0.04) and serum transferrin (Δ 4.7 mg/dL vs Δ −0.7 mg/dL, p = 0.0007). The increase in QoL was significantly higher in SUPL group. Dry weight was achieved in 100% of patients in SUPL and 95% in CON group. Conclusions: ONS combined with BIVA for dry weight adjustment, improved nutritional status, QoL and achieved dry weight in HD patients. Graphical abstract: Image 1 Highlights: PEW and OH occur simultaneously in hemodialysis patients and increase mortality and decrease quality of life. There are no simultaneous interventions to correct undernutrition and overhydration in hemodialysis patients. Simultaneous intervention of ONS and dry weight correction through BIVA improves nutritional status, hydration and QoL. This intervention can have an impact on outcomes, such as reduced mortality, and could be a cost-effective strategy. BIVA is a less invasive, more cost-effective technique than other strategies used to reach dry weight.